Strategic asset management framework for the improvement of large scale PV power plants in Australia - Shah, S.; Mahmood, M.; Das, Narottam (2016)
© 2016 IEEE. The stringent environmental regulations and higher energy demands due to increasing population are main concerns for the energy industries. In order to comply with the environmental regulations and also to improve the energy supply of large scale photovoltaic (PV) power plants are developing rapidly as an alternative energy source to fossil fuels. Management of large scale PV power plants has become a challenging issue mainly due to the absence of less structured strategic asset management framework. This paper has addressed to this gap and proposed a well-structured strategic asset management framework for large scale PV power plants. The study have also pointed out that due to lack of clear policies and without having a specific framework for PV or solar assets, Australia is lagging behind in the production of solar energy than Europe and Asian countries despite having highest solar radiation per kilometer square. The proposed framework will provide a basis for understanding the current status of individual solar farms and the way forward to improve the asset management capabilities.